A combination of early warning score and lactate to predict intensive care unit transfer of inpatients with severe sepsis/septic shock - Yoo, Jung-Wan; Lee, Ju Ry; Jung, Youn Kyung; Choi, Sun Hui; Son, Jeong Suk; Kang, Byung Ju; Park, Tai Sun; Huh, Jin-Won; Lim, Chae-Man; Koh, Younsuck; Hong, Sang Bum (The Korean journal of internal medicine, 2015)
The modified early warning score (MEWS) is used to predict patient intensive care unit (ICU) admission and mortality. Lactate (LA) in the blood lactate (BLA) is measured to evaluate disease severity and treatment efficacy in patients with severe sepsis/septic shock. The usefulness of a combination of MEWS and BLA to predict ICU transfer in severe sepsis/septic shock patients is unclear. We evaluated whether use of a combination of MEWS and BLA enhances prediction of ICU transfer and mortality in hospitalized patients with severe sepsis/septic shock. Patients with severe sepsis/septic shock who were screened or contacted by a medical emergency team between January 2012 and August 2012 were enrolled at a university-affiliated hospital with ~2,700 beds, including 28 medical ICU beds. One hundred patients were enrolled and the rate of ICU admittance was 38%. MEWS (7.37 vs. 4.85) and BLA concentration (5 mmol/L vs. 2.19 mmol/L) were significantly higher in patients transferred to ICU than those in patients treated in general wards. The combination of MEWS and BLA was more accurate than MEWS alone in terms of ICU transfer (C-statistics: 0.898 vs. 0.816, p = 0.019). The 28-day mortality rate was 19%. MEWS was the only factor significantly associated with 28-day mortality rate (odds ratio, 1.462; 95% confidence interval, 1.122 to 1.905; p = 0.005). The combination of MEWS and BLA may enhance prediction of ICU transfer in patients with severe sepsis/septic shock.